Security Evaluation of Provably Secure ECC-Based Anonymous Authentication and Key Agreement Scheme for IoT - Kisung Park; Myeonghyun Kim; Youngho Park (Sensors)
The proliferation of the Internet of Things (IoT) has worsened the challenge of maintaining data and user privacy. IoT end devices, often deployed in unsupervised environments and connected to open networks, are susceptible to physical tampering and various other security attacks. Thus, robust, efficient authentication and key agreement (AKA) protocols are essential to protect data privacy during exchanges between end devices and servers. The previous work in “Provably Secure ECC-Based Anonymous Authentication and Key Agreement for IoT” proposed a novel AKA scheme for secure IoT environments. They claimed their protocol offers comprehensive security features, guarding against numerous potential flaws while achieving session key security. However, this paper demonstrates through logical and mathematical analyses that the previous work is vulnerable to various attacks. We conducted a security analysis using the extended Canetti and Krawczyk (eCK) model, which is widely employed in security evaluations. This model considers scenarios where an attacker has complete control over the network, including the ability to intercept, modify, and delete messages, while also accounting for the potential exposure of ephemeral private keys. Furthermore, we show that their scheme fails to meet critical security requirements and relies on flawed security assumptions. We prove our findings using the automated validation of internet security protocols and applications, a widely recognized formal verification tool. To strengthen attack resilience, we propose several recommendations for the advancement of more robust and efficient AKA protocols specifically designed for IoT environments.